88.6k views
9 votes
3(x+ 7) = -12
x + 7 =
X =

3(x+ 7) = -12 x + 7 = X =-example-1

2 Answers

7 votes

Answer:

x = - 11

x + 7 = -4

Explanation:


3(x + 7) = - 12

Multiply each term in parentheses by 3


3x + 3 * 7 = - 12

Multiply 3 and 7


3x + 21 = - 12

Move the constant to the right side and change the sign


3x = - 12 - 21

Find the sum of negative numbers


3x = - 33

Divide both side by the same number


x = - 11

= x + 7

= -11 + 7

Add the term - 11 + 7

= -4

User Martin Magakian
by
5.0k points
7 votes

Hey ! mate

Answer:

  • x + 7 = -4

  • x = -11

Explanation:

In this question we have given an equation that is 3( x + 7 ) = -12 and we have asked to find the value of x + 7 and x .

We are starting our solution from here :


\longmapsto \: 3( x + 7 ) = -12

Transposing 3 to right hand side :


\longmapsto \: x + 7 = ( - 12)/(3)

Now , dividing -12 by 3 :


\longmapsto \: \blue{\boxed{x + 7 = -4}}

  • Therefore , value of x + 7 is - 4 .

Now ,


\longmapsto \:x + 7 = - 4

Transposing 7 to right hand side :


\longmapsto \:x = - 4 - 7


\longmapsto \: \blue{ \boxed{x = - 11}}

  • Therefore , value of x is -11 .

#Keep Learning

User RomanKonz
by
5.3k points